Insights into teaching a complex skill: Threshold concepts and troublesome knowledge in electroencephalography (EEG). (3rd April 2018) - Moeller, Jeremy J.; Fawns, Tim
Abstract: Background: Threshold concepts (TCs) are defined as ideas within a discipline that are often conceptually difficult ("troublesome"), but when learned, transform a learner's understanding. Electroencephalography (EEG) has been recognized as a conceptually difficult field in neurology, and a study of threshold concepts in EEG may provide insights into how it is taught and learned. Methods: Semi-structured interviews were performed with 12 EEG experts in the US and Canada. Experts identified potential TCs and troublesome knowledge, and explored how these concepts were taught and learned. Interview transcripts were coded and analyzed using a general thematic analysis approach, based on the core elements of the threshold concepts framework. Results: One concept (polarity) emerged most clearly as a threshold concept. Other troublesome areas included pattern interpretation and clinical significance, but these lacked some of the characteristics of TCs. Several themes emerged, including the role of TCs and troublesome knowledge in determining expertise and the role of prior experience. Conclusions: We have used the threshold concepts framework to explore potential barriers to learning, suggest ways to support learners, and identify potential points of emphasis for teaching and learning EEG. A similar approach could be applied to the study of teaching and learning in other conceptually difficult areas of medical education.